Pengaruh Penambahan High Performance Superplasticizer terhadap Kuat Tekan Mortar - Putri, Delfia Diana; Suhendra, Suhendra; Zulfiati, Ria; Fadlan, Fadlan (Jurnal Talenta Sipil, 2025)
Currently, the development of innovation regarding concrete mortar mix design technology is being widely researched. The innovation in making mortar is the use of additives. This research aims to determine the effect of adding additives on the workability and compressive strength of mortar. The additive used is a High Performance Superplasticizer with the trademark Sika Viscocrete 8670 MN. The fine aggregate used is ex sand. Batang Hari River. The sand category used is coarse sand, based on ASTM C33. The mortar test object is in the shape of a cube with dimensions of 5x5x5 cm. The test specimens consisted of Normal Mortar (MN), Mortar with 0.6% Sika Viscocrete (MS 0.6%), and Mortar with 1.4% Sika Viscocrete (MS 1.4%). The compressive strength testing method refers to SNI 03-6825-2002 concerning Testing Methods for Compressive Strength of Portland Cement Mortar. The results of testing organic dirt in the coarse sand of the Batanghari River are unwashed sand at number 3, and sand that has been washed and soaked with 3% NaOH at number 2 on the organic plate. The compressive strength test results at 8 hours of MN were 6.97 MPa, MS 0.6% was 6.70 MPa and MS 1.4% was 7.73 MPa. The compressive strength at 1 day of age for MN was 14.68 MPa, MS 0.6% was 16.27 MPa, and MS 1.4% decreased to 14.28 MPa. The compressive strength at 7 days of MN was 19.93 MPa, MS 0.6% was 25.33 MPa, and MS 1.4% was 26.95 MPa. Compressive strength at the age of 28 days, MN's compressive strength value is superior, namely 31.53 MPa, MS 0.6% is 28.72 MPa and MS 1.4% is 28.80 MPa. The research results show that to maintain the workability of mortar mixtures that use high performance superplasticizer additives, it is necessary to reduce water. At 28 days, normal mortar has superior compressive strength compared to mortar that uses high performance superplasticizer as added material.